Avaliação da atividade bactericida do biovidro F18 e F18 com prata para aplicações médicas - Campanini, Lidiani Aparecida (Universidade Federal de São Carlos, 2015)
Millions of surgeries for implants and prosthesis placement are performed annually worldwide. Among these surgical procedures are observed some types of failures. The most worrying complication is the infection that can cause deformity in the region, amputation of body parts, and may progress to osteomyelitis and patient death. In this context, the bactericidal property of the bioactive glasses is being widely studied. The F18 is a new bioglass that was developed at Vitreous Materials Laboratory (LaMaV) and can be manipulated in different forms to be used as auxiliary agent in the medical treatment of infectious processes. The purpose of this study was to investigate the bactericidal activity of F18 in powder form for coating implants and in fibers form to be used in wound healing, on the bacteria Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli and Pseudomonas aeruginosa. In addition, it was proposed to compare the kinetic of bactericidal activity of F18 in powder, F18 in powder doped with silver (F18Ag), and the standard bioglass called 45S5, on S. aureus. The bactericidal activity of F18 was tested using an analysis method based on a standard JIS (Japanese Industrial Standard) Z2801: 2010, where the inoculum was in contact with the material for 24 hours and the reduction of viable cells was observed after this period. For the realization of kinetic tests the powder samples from different materials were placed in contact with the S. aureus suspension and an aliquot of these mixtures was plated in a culture media at different times. The direct count of colony on Petri dishes demonstrated the viable cells reduction. F18 both in powder form and in the form of fibers showed an extremely efficient bactericidal activity. The elimination of the microorganisms was close to 100%. The log of reduction of bacteria was between 5.9 ± 0.4 and 7.0 ± 0.2 log10 CFU ml-1, and the standard considers as a bactericide the material that shows a reduction of 2.0 logs or more. The bactericidal activity of F18Ag began after the first 30 minutes of contact with microorganisms and practically eliminated the bacterial colonies after one hour of contact. The bactericidal action of F18 started after six hours and eliminated viable cells after 24 hours. Both materials demonstrated bactericidal action similar to that presented by the standard 45S5.
Keywords: Implantes; Infecção de sítio cirúrgico; Biovidro; Atividade bactericida; Prata; Implants; Surgical site infection; Bioglass; Bactericidal activity; Silver; CIENCIAS EXATAS E DA TERRA